Exploration of key traction-running equipment and its problems on heavy-haul trains and research on technology development. Issue 3 (29th August 2020) - Chen, Chunyang; Li, Wei; Liu, Youmei; Wei, Xiang
Abstract: In recent years, heavy-haul train technology has seen a number of innovations worldwide, and train traction-running technology has also made great progress, resulting in a rich pool of experience and a range of promising applications. This paper summarizes the key technologies of traction running in heavy-haul combined trains, especially locomotive and rolling-stock technology, traction technology, braking technology, control technology, communication technology and safety technology. At the same time, based on an analysis of practical applications, this paper further explores the main problems and urgent needs of traction equipment on heavy-haul trains. With an eye to the future, the heavy-haul railway system will develop in the direction of informatization, automation and intelligence, in order to build a greener, more energy-saving, safer and more efficient railway. This paper therefore looks forward to the technical developments of heavy-haul combined trains, and provides a reference for the development of heavy-haul railways.